Direct relationships between volume variations at macro and nanoscale in epoxy systems. PALS/PVT measurements - Goyanes, Silvia Nair (2004)
The free volume in epoxy systems fully cured with aminic hardeners having different chemical structures was studied by means of positron annihilation lifetimes spectroscopy. The results are compared with those obtained from the analysis of the macroscopic specific volume changes by using pressure-volume-temperature experimental technique. An excellent correlation between the volumes measured at macro and nanoscales was found. From this fact, it can be asserted that the variation of the specific volume is mainly controlled by the variation in the average size of sub-nanometer size local free volumes, which are fixed by the chemical structure of hardener in fully crosslinked epoxy networks. These results give the first evidence of the direct relation existing between macro and nanoscales in thermosetting networks. © 2004 Elsevier Ltd. All rights reserved.